2012
DOI: 10.1103/physrevlett.109.097404
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Photoluminescence Excitation and Recharging Cycle of Single Nitrogen-Vacancy Centers in Ultrapure Diamond

Abstract: Important features in the spectral and temporal photoluminescence excitation of single nitrogen-vacancy (NV) centers in diamond are reported at conditions relevant for quantum applications. Bidirectional switching occurs between the neutral (NV(0)) and negatively charged (NV(-)) states. Luminescence of NV(-) is most efficiently triggered at a wavelength of 575 nm which ensures optimum excitation and recharging of NV(0). The dark state of NV(-) is identified as NV(0). A narrow resonance is observed in the excit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
156
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(173 citation statements)
references
References 23 publications
16
156
1
Order By: Relevance
“…Previous experiments demonstrated that the charge-state conversion is mainly a two-photon process with a laser wavelength longer than 500-nm. 25,30,36 The NV is first pumped to the excited state of NV 2 or NV 0 ; then, an electron is released to the conduction band during ionization or captured from the valance band during recharging. 24 The nonlinear power dependence of the conversion rates in Figure 1f was obtained by repeating the measurement of Figure 1d with different laser powers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous experiments demonstrated that the charge-state conversion is mainly a two-photon process with a laser wavelength longer than 500-nm. 25,30,36 The NV is first pumped to the excited state of NV 2 or NV 0 ; then, an electron is released to the conduction band during ionization or captured from the valance band during recharging. 24 The nonlinear power dependence of the conversion rates in Figure 1f was obtained by repeating the measurement of Figure 1d with different laser powers.…”
Section: Resultsmentioning
confidence: 99%
“…For the same power, the charge-state conversion rate of the 532-nm laser is higher than that of the 637-nm laser, as observed in Figure 1f, which might result from the wavelength-dependent absorption cross-section of the NV center at room temperature. 25,36 Therefore, the resolution of iCSD is better than that of rCSD for the same power and duration of the D laser. In reality, the improvement of the CSD resolution remains limited by the power of the laser and stability of the piezo stage.…”
Section: Csd Microscopymentioning
confidence: 99%
“…Even at 9K, only 4% of the fluorescence is emitted into the ZPL which exhibits a narrow, ideally lifetime limited linewidth (13 MHz, [39] ) at low temperature; Coupling of NV centers to a photonic structure has thus either to be broadband or has to overcome the emission into the sideband by a highly efficient coupling [40] . NV centers have a lifetime of 12 ns in bulk [41] , the emitted light is only partially polarized [42] and efficiency can be limited by switching to the neutral charge state [43] . There is therefore an ongoing quest to identify and characterize other emitters for photonic applications.…”
Section: Nv Centersmentioning
confidence: 99%
“…This result reveals the existence of a significant source of electric field noise. It is known that a two-photon ionization process of the NV defect can promote charge carriers to the conduction band of diamond [30][31][32] . This mechanism was recently used to demonstrate photoelectric detection of the electron spin resonance 33 .…”
mentioning
confidence: 99%